“WhatsApp” sebagai media telekonsultasi dalam upaya pemantauan tumbuh kembang balita di masa pandemi COVID-19 - Sari, Indah Purnama; Yuliarti, Yuliarti; Ningsih, Windi Indah Fajar; Ermi, Nurmalia; Ardillah, Yustini (Fakultas Kedokteran Universitas Sriwijaya, 2022)
The COVID-19 pandemic has had an impact on child health services at the posyandu, especially monitoring growth and development. The proportion of toddlers who are stunted will increase not only in Indonesia but also in Palembang if children had growth and development disorders that are not monitored as the Posyandu was temporarily closed during the pandemic. WhatsApp can be used as a medium for teleconsultation in an effort to monitor the growth and development of toddlers. This activity provided education to mothers who have toddlers through teleconsultation in the form of information, motivation and solutions for monitoring the growth and development of children. This activity was carried out online using the WhatsApp application by recruiting 37 women in the Whatsapp group. The results of the activity showed that WhatsApp can be used as a teleconsultation media in educating mothers in an effort to monitor the growth and development of toddlers during a pandemic as the Posyandu was temporarily closed. The mother's enthusiasm can be seen from the active teleconsultation process in the WhatsApp group. Through this activity, it concluded that WhatsApp can be used as a teleconsultation media to monitor children's growth even though the mother did not directly receive education at the Posyandu.